Exploring change in the relative abundance of marine megafauna in the Bay of Biscay, 2004–2016. (September 2018) - Authier, Matthieu; Dorémus, Ghislain; Van Canneyt, Olivier; Boubert, Jean-Jacques; Gautier, Gérard; Doray, Mathieu; Duhamel, Erwan; Massé, Jacques; Petitgas, Pierre; Ridoux, Vincent; Spitz, Jérôme
Highlights: Monitoring biodiversity is essential to marine conservation in Europe. Marine megafauna (cetaceans and seabirds) are important nodes in foodwebs. Trajectories of megafauna relative abundance in the Bay of Biscay were contrasted. Offshore species tended to increase in relative abundance over the study period. One third of the studied species tended to decrease between 2004 and 2016. Abstract: Conservation has moved from species-centered to ecosystem-based approaches: the Marine Strategy Framework Directive requires the maintenance or restoration of 'Good Environmental Status' of all European marine waters. Monitoring biodiversity at the scale of whole ecosystems is salient, but challenging owing to the large spatial scale involved and the large spatio-temporal heterogeneity of marine ecosystems. We capitalized on the integrated ecosystemic PELGAS survey carried out in spring in the Bay of Biscay to document patterns of change in marine megafauna relative abundance at the community level over more than a decade (2004–2016). The relative abundance of the twenty-three most frequently sighted species (6 cetaceans and 17 seabirds) was estimated by distance sampling, and averaged over the study period and area. Temporal changes were investigated with a Dynamic Factor Analysis. This exploratory analysis suggested that approximately one third of all species showed an increase, another third a decrease, and the last third no overall change in relative abundance. The relative abundance of offshore species, including that of all studied cetaceans, slightly increased in spring between 2004 and 2016. Further investigations will correlate the uncovered changes at the marine megafauna community level with concommittent biological and oceanographic processes that are routinely monitored on the PELGAS integrated ecosystemic surveys.